Modeling progressive collapse of 2D reinforced concrete frames subject to column removal scenario - Weng, J.; Tan, K.H.; Lee, C.K. (Engineering structures, 2017)
•A new modeling procedure for progressive collapse of 2D RC frame are developed.•Effects of service loads before column removal are considered.•Algorithms detecting substructure collapse and collapse impacts are proposed.•Performance of the proposed procedure demonstrated by numerical examples. In this study, a new modeling procedure for progressive collapse analysis of 2D reinforced concrete (RC) frames subject to single or multiple column removal scenario is proposed. Different from traditional pushdown analysis, the proposed method incorporates the effects of service loads before column removal into the analysis. To trace the collapse sequence of the structure, a member removal algorithm based on combined actions of flexural/shear/axial failures is employed. For detecting substructure collapse mechanisms, a specially designed searching algorithm is developed. Furthermore, the locations and magnitudes of collapse impacts are respectively determined by rigid-body kinematics and energy principle with both inelastic and oblique impact effects considered. Numerical examples with different loading and column removal scenarios are given to validate the suggested damage assessment procedure, the member failures identification procedure and the collapse searching algorithms as well as to demonstrate the effectiveness of the proposed modeling approach.